The Impact of Free Zones on Foreign Trade: An Empirical Application by using ARDL Model on Turkey - Oncel, Abidin; Demirtas, Sukru Can (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2017)
Free trade zones are established to gain advantage in foreign trade. In theory, it is expected to see a positive impact in foreign trade if there is an increase in free trade zones' trade. Thereby, this study examines the relationship between free trade zones and foreign trade of Turkey empirically by using ARDL model. Existence of said relationship has been confirmed for both long and short terms for 2000:01-2015:12 period. Hereunder, in the short term 1% change in import of free trade zones increase Turkey's import by 0,12% while 1% change in export of free trade zones increase Turkey's export by 0,47%. In the long term, no meaningful relationship has been found between imports of free trade zones and Turkey's import rate however, 1% change in export of free trade zones increases Turkey's export by 0,14%. Informations obtained shows that free trade zones contribute greatly specifically to the export of Turkey.
Keywords: Free Zones; Cointegration; ARDL model; Foreign Trade; UNIT-ROOT; INCOME; FIJI; Business & Economics